Model Pengembangan Desain Instruksional Pada Materi Fluida Statik - Harahap, Aminah (Institut Agama Islam Negeri Padangsidimpuan, 2024)
The research carried out is related to assessing the use of learning models. The learning model used is the Instructional Design development model on Static Fluid material in Class XI SMA Negeri 1 Batangtoru. This model requires students to be more active in class. The use of this model will be combined with the use of modules as a learning resource, so that it can become an alternative for implementing learning. The aims of this research are 1) to describe learning using modules as an effective learning resource, 2) to describe student activities while using the Instructional Design Development Model in Static Fluid material in Class XI SMA Negeri 1 Batangtoru with modules as a learning resource, 3) to describe the results student learning while using the Instructional Design development model in Static Fluid material in Class Learning Resources.This research is action research which is developmental and pre-eliminary in nature, so it only uses one class. The research design uses Kemmis MC Taggart's cycle model with a One Group Pretest-Posttest Design learning pattern. This research was carried out at SMA Negeri 1 Batangtoru class XI MIPA1, with 34 students. This learning consists of three cycles. The implementation of learning in each cycle uses different syntax, so that you can find out which cycle is most effective. Student learning activities are divided into three stages, Instruction stage, Doing stage, and Evaluating stage. Student learning activities increase in each cycle. Student activities are in the active to very active category. The highest student activity is in cycle 3 with the very active category. Student scores increase from pretest to posttest in each cycle. The highest posttest average score was in cycle 2. The highest n-gain was also in cycle 2 with the medium category. Student learning retention is included in the very strong category. The most effective learning uses the Instructional Design development model in Static Fluid material in Class XI SMA Negeri 1 Batangtoru with modules as learning resources located in cycle 2. Based on the analysis of research data results, it can be concluded that the Instructional Design development model for Static Fluid material in Class XI SMA Negeri 1 Batangtoru with modules as learning resources is suitable for use in Static Fluid material in Class This model can be an alternative learning model implemented by teachers. This research requires thorough preparation, so that further research can be better prepared